IMPLEMENTATION OF THE YANBU'A METHOD TO INCREASING ELOQUENCE RECITING AL-QUR'AN SANTRI TPQ FATCHUL ULUM PACET - Ishmatun Nihayah; Wagini Wagini (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2022)
Abstract The purpose of this article is to describe the planning, implementation, and evaluation of the Yanbu'a Method at TPQ Fatchul Ulum Pacet. This article uses a type of qualitative research with a case study approach. For data collection, researchers used observations, interviews, and documentation techniques. This study obtained the following results: 1) general learning planning a) Class classification. b) Selection test. c) Teacher training and determination. d) Schedule creation. e) Procurement of learning tools and media. f) Material preparation. g) Giving evaluation. 2) Implementing the Yanbu'a method in improving the fluency of reading the Qur'an of students at TPQ Fatchul Ulum Pacet a) Consists of three stages, namely pre-instructional, instructional and closing or assessment b) Using the classical system, individual reading, and classical reading system. Evaluation of the implementation of the Yanbu'a method in improving the fluency of reading the Qur'an of students at TPQ Fatchul Ulum; a) The page increase test. b) Volume increase test. c) Imtihan Niha'iy.